Upaya Pemberdayaan Pendidikan Dan Kepedulian Masyarakat Tentang Lingkungan di Dusun Gupak Warak - Lagosa, I Wayan Tio; Sidik, Rifky Muhammad; Mohandes, Raynard Haryono; Ramadhan, Najmi Hibatullah; Mudzakir, Azis; Hendrwan, Nadiva Syabilla Sari; Nihayah, Ade Isma Maula; Vega, Amelia; Holijah, Siti; Az Zahra, Fatimah; Handayani, Siti Dyah (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Community service in Gupak Warak Hamlet aims to increase public awareness of the environmental and social issues in the area. One of the main problems faced is the low awareness of the community in managing waste, which leads to the habit of burning trash in open areas, such as yards, rather than disposing of it in the provided waste bins. The practice of open burning not only pollutes the environment but also poses potential health risks due to the harmful smoke and particles generated. Additionally, bullying behavior was found among students at the local Madrasah Ibtidaiyah (MI). Bullying in the school environment can negatively impact children's psychological development, lower self-esteem, and disrupt the comfort of the teaching and learning process. To address these issues, a community service program was carried out using socialization and training methods directed at the community and MI students. Socialization and training for the community aim to increase understanding of the negative impacts of waste burning, the importance of organic and inorganic waste management, and the implementation of recycling methods. On the other hand, socialization and training for MI students are intended to raise awareness about the harmful effects of bullying. This activity is expected to promote positive thinking regarding waste management, reduce the practice of waste burning that harms the environment, and create a safer and more comfortable school environment for students. With this program, it is hoped that behavioral changes will occur in both the community and MI students, leading to the creation of a healthier, safer, and more harmonious environment in Gupak Warak Hamlet